توظيف السرد العربي في الخطاب الإعلامي المكتوب - قعيد, خليفة (University of Eloued جامعة الوادي, 2021)
يتجلّى السرد العربي بمختلف صيغه وأنواعه التخييلية وغير التخييلية في الخطاب الإعلامي. وقد سمح تكامل العلوم الاجتماعية والإنسانية بملاحظة التداخلات الأجناسية فيما بين السرود والخطابات على غرار السرد الأدبي، والسرد السينمائي، والسرد الفلسفي، والسرد التاريخي، والسرد القرآني، والسرد النفسي والعلاجي، والسرد الإعلامي وغيرها. ويعتبر السرد العربي من بنوعيه التخييلي وغير التخييلي أكثرها تجليا في الخطاب الإعلامي المكتوب بسبب حاجة صاحب الخطاب الإعلامي إلى توظيفه قصد التأثير على المتلقي لعدة أهداف مستعملا في ذلك وسائل الإعلام المكتوبة، الورقية والإلكترونية باعتبار توفرها على قوة ترويجية وتأثيرية جماهيرية. وقد طرحت الدراسة الإشكالية التالية: لماذا وكيف يتم توظيف السرد العربي في الخطاب الإعلامي المكتوب؟ وقد خاضت الدراسة في هذا الموضوع الذي مازال بكرا في الدراسات العربي؛ وذلك قصد حلحلته من خلال تطبيق مقاربات بنيوية سردية، وسميائية وتداولية. وقد بيّنت الدراسة أن خطاب السرد العربي والخطاب الإعلامي المكتوب يقوم كلاهما على متن حكائي يمثّل الخبر أو القصة الخبرية، وعلى شكل تعبيري يمثّل المبنى الحكائي. ويتجلى السرد العربي في الخطاب الإعلامي المكتوب من خلال صيغ متعددة منها الاستعارة والكناية، والمثَل والحكاية المثلية، والتوقيعة، والتناصّ، والتعالق النصّي، والقصص الواقعي الحقيقي، التاريخي، والقرآني، والفلسفي...الخ. وقد أطلقت الدراسة على جميع تجليّات السرد العربي في الخطاب الإعلامي تسمية موحّدة هي لفظ «السريدة»؛ وهي كلمة أنعشتها هذه الدراسة لكي تؤدي غرضا أساسيا فيها مادامت تنتمي إلى الحقل المعجمي للسرد. ويؤدي السرد العربي في الخطاب الإعلامي المكتوب عدة وظائف هامة تتمثل في السردية، الوظيفة الحجاجية، الوظيفة الإعلامية، الوظيفة الإيديولوجية، الوظيفة الإغرائية، الوظيفة الفنية، الوظيفة الثقافية، الوظيفة الاستشهادية، الوظيفة السيميائية وغيرها. و قد وضّحت الدراسة مختلف أنظمة القوالب السردية التي يقوم عليها سرد الخطاب الإعلامي، كما قدمت عدة نماذج تطبيقية لصيغ وتراكيب السرد العربي المحتضَن في الخطاب الإعلامي الحاضن بما فيها السرد العربي المنحوت في كلمة واحدة؛ حيث تمت دراستها من ناحية البنية السردية اللسانية، والسيميائية مع وضع توليفة من عدة نظريات سردية وسيميائية لدراسة بعض نماذج السرد العربي المتجلية في الخطاب الإعلامي بصيغة نحت سردي في كلمة واحدة، بالإضافة إلى القيام بدراسة تداولية على السرد العربي شملت النظام التركيبي، والتعابير الإشارية، ومبدأ التعاون بين المرسل والمرسل إليه، ونظرية الأفعال الكلامية. The arabic narration, in its fictional and non-fictional forms, is manifested in the media discourse through multiple and various moods. The complementary of the social and human sciences allowed to observe of the interactions of genres between narratives and discourses such as literary narration, cinematic narration, philosophical narration, historical narration, Quranic narration, psychological and therapeutic narration, media narration, and others. The Arabic narration of both fictional and non-fictional types is the most manifested in the written media discourse due to the need for the enunciator to employ it in order to influence the recipient for several goals using both written paper and electronic media that have a great public influence. This study propose the following problematic: Why and how is the Arabic narrative employed in written media discourse? The studies into this topic are still new in Arabic studies. Thus, This study was intended to study it through applying structural, narrative, semiotic and pragmatic approaches. The study showed that both the Arabic narrative discourse and the written media discourse are based on a narrative content that represents the news or news story, and in an expressive form that represents the narrative form. The arabic narration manifests in the written media discourse through multiple moods such as metaphors, proverbs and fable, signature, intertextuality, transtextuality, and fictional and non-fictional stories as real, historical, Quranic, and philosophical stories ... etc. This study used a unified term: «Sarida» (account) to name any the manifestation mood of the arabic narration in the media discourse. It is an arabic word revitalized by this study in order to fulfill a basic purpose as long as it belongs to the lexical field of the arabic narration. The arab narration in written media discourse performs several important functions, which are the narrative function, the argumentative function, the communicative function, the ideological function, the attractive function, the artistic function, the cultural function, the testimonial function, the semiotic function, and others. The study clarified the various systems of narrative templates on which the narrative of the media discourse is based. It also presented several applied models for the forms and structures of the arabic narrative incubated in media discourse, including the arabic narration carved into one word. These models were studied in the view of a linguistic and narrative structure and semiotics. The study developed a combination of several narrative and semiotic theories to study some arabic narrative models manifested in media discourse in the form of narrative carving in one word, in addition to conducting a pragmatic study on the arabic narration that included the syntax system, indicative expressions, and the cooperation principle between the transmitter and the receiver, and pragmatics speech act theory.
أطروحة دكتوراه في علوم اللغة العربية تخصص السرد العربي
Keywords: السرد، السريدة، السرد العربي، السرد الإعلامي، البنية السردية، الخطاب، سيمياء السرد، تداولية السرد; Narration, Account, Arabic Narration, Narrative Structure, Discours, Narrative semiotics, Narrative pragmatics, Media Narration